Adapting the TSA to measure the economic contribution of tourism in Serbia - Jovanović, Verka; Vukasović, Slađana (The European Journal of Applied Economics, 2014)
The Tourism Satellite Account (TSA) enables estimating the direct contribution of tourism consumption to the national economy. The World Tourism Organization (UNWTO), the Organization for Economic Cooperation and Development (OECD) and the Statistical Office of the European Communities (Eurostat) have proposed the methodological framework for Tourism Satellite Account. The United Nations Statistical Commission (UNSC) approved its use in March 2000. Conceptually, TSA is compliant with other statistical frameworks such as the System of National Accounts (SNA) and the Balance of Payments (BOP) and it links tourism statistics and the SNA standard tables. The main objective of the TSA is to provide a better understanding of the scope and value of the tourism industry in Serbia, based on the figures and data that can be compared at an international level and whose reliability is very high since they are based on the quality of the official national statistics.